The Effect of Compensation and Work Environment on Employee Performance Mediated by Motivation: - Rivha Endhah Anggraeny; Didik Subiyanto; Epsilandri Septyarini (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Service Bantul City's culture is device formed area - in skeleton carry out affairs government field culture and assignments affairs privileges of the Special Region of Yogyakarta. The objective of the study is To analyze and find out the influence of compensation and environmental work on the performance of employees mediated by Motivation. Study this using research that is quantitative whereas in getting data used instrument research that has been set with spread questionnaire, check or checklist to respondents. In research, this use technique of nonprobability sampling (saturated sampling) is a technique determination sample when all member populations are used as the sample that is whole employee Service Culture Bantul Regency consists of 30 people. The research results obtained variable compensation no influential positive however significant to variable motivation, variable environment work influential positive and significant to variable motivation, variable motivation influential positive and significant to variable performance employee, variable compensation influential positive and significant to variable performance employee, variable environment work influential positive and significant to variable performance employee, motivation influential direct as well as could mediate compensation to performance employee as well as motivation influential direct as well as could mediate environment work to performance employee. Keywords: compensation, motivation, environment work, performance employee, mediation